Information Acquisition and Welfare. (20th June 2014) - Colombo, Luca; Femminis, Gianluca; Pavan, Alessandro
Abstract: We study information acquisition in a flexible framework with strategic complementarity or substitutability in actions and a rich set of externalities that are responsible for possible wedges between the equilibrium and the efficient acquisition of information. First, we relate the (in)efficiency in the acquisition of information to the (in)efficiency in the use of information and explain why efficiency in the use is no guarantee of efficiency in the acquisition. Next, we show how the acquisition of private information affects the social value of public information ( i.e . the comparative statics of equilibrium welfare with respect to the quality of public information). Finally, we illustrate the implications of the results in a monetary economy with price rigidities and dispersed information about productivity shocks.